Search for a light pseudoscalar Higgs boson produced in association with bottom quarks in pp collisions at root s=8 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; et al. (JOURNAL OF HIGH ENERGY PHYSICS, 2017)
A search for a light pseudoscalar Higgs boson (A) produced in association with bottom quarks and decaying into a muon pair is reported. The search uses 19.7 fb−1 of proton-proton collisions at a center-of-mass energy of 8 TeV, collected by the CMS experiment. No signal is observed in the dimuon mass range from 25 to 60 GeV. Upper limits on the cross section times branching fraction, σ(pp→bb¯¯¯A)B(A→μμ), are set.